2008
DOI: 10.3177/jnsv.54.321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grape Seed Proanthocyanidin Extracts on Peripheral Nerves in Streptozocin-Induced Diabetic Rats

Abstract: Summary Diabetic peripheral neuropathy (DPN) is one of the most common diabetic chronic complications. The aim of this study was to clarify whether grape seed proanthocyanidins extracts (GSPE) are therapeutic agents against DPN. In this study, we used streptozocin (STZ) to induce diabetic rats. GSPEs (250 mg/kg body weight/d) were administrated to diabetic rats for 24 wk. Motor nerve conductive velocity (MNCV) and mechanical hyperalgesia were determined in the rats. Serum glucose, glycated hemoglobin, advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 32 publications
(25 reference statements)
8
53
2
Order By: Relevance
“…Uchida et al reported that GSPE had a significant antinociceptive effect in mice during the formalin test (Uchida et al, 2008), and Cui et al showed that GSPE plays a protective role against diabetic peripheral neuropathy by ameliorating nerve damage associated with oxidation (Cui et al, 2008). These results suggest that GSPE has an antinociceptive effect.…”
Section: Discussionsupporting
confidence: 55%
“…Uchida et al reported that GSPE had a significant antinociceptive effect in mice during the formalin test (Uchida et al, 2008), and Cui et al showed that GSPE plays a protective role against diabetic peripheral neuropathy by ameliorating nerve damage associated with oxidation (Cui et al, 2008). These results suggest that GSPE has an antinociceptive effect.…”
Section: Discussionsupporting
confidence: 55%
“…The superoxide anion scavenging activity of GSPE was stronger than vitamin C, vitamin E or any other antioxidant. 1) It has been reported to have protective effects on various cardiac disorders, correct dyslipidemia associated with high-fat diet, 2) decrease arterial pressure in estrogen-depleted female spontaneously hypertensive rats, 3) prevent diabetic nephropathy and neuropathy from progressing, 4,5) and most importantly, ameliorate atherosclerosis, 6) possibly attributed to its endothelial protective potential.…”
mentioning
confidence: 99%
“…These results suggest that these animals suffered growth retardation due to the hindrance of glucose uptake (26) but oral GSE supplementation did not affect body weight in diabetic rats. Although in recent studies (14,26,27) it has been suggested that oral GSE supplementation increased body weight changes in diabetic rats compared to the untreated diabetic controls, in these studies the GSE dosage was larger (250 mg kg -1 day -1…”
Section: Discussionmentioning
confidence: 67%